SOME MAIN CONCLUSIONS DRAWN FROM A BASINAL ANALYSIS OF THE DWYKA SERIES IN THE KARROO BASIN - Stratten, T. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1968)
The research fell mainly into two separate but related fields of study. The first field was to investigate the pre-Karroo surface with special reference to the geology beneath the Karroo System. The second field was to investigate the paleo-ice flow directions of the Dwyka Tillite and relate this to the position and lithology of the source areas.